UPAYA PENINGKATAN PENGETAHUAN SISWA SEKOLAH DASAR MENGENAI JAJANAN SEHAT DAN MAKANAN BERGIZI DI SDN 03 BUKIT TAMBUN TULANG - Rahmaddiansyah, Refa; Nurmiati, Nurmiati; Rusti, Sukarsi; Fettriwanti, Fettriwanti; Hendra, Gabriel Septian (Universitas Methodist Indonesia, 2023)
Over the past few decades, new approaches to health promotion have been developed. The target of health promotion is all ages, including children. Elementary school-age children do not yet know what is good for their physical health, including choosing healthy snacks. Consuming unsafe food can cause health problems in groups of people, leading to increasing health disparities globally. Children buy snacks based on their preferences without paying attention to the food ingredients. Children still have relatively little knowledge about healthy snacks. The aim of this activity is to provide outreach to educate elementary school-age children about healthy snacks and the importance of balanced nutrition. Community service activities were carried out on July 28 2021 from 07.30 WIB to 10.30 WIB in the classrooms of SD Negeri 03 Bukit Tambun Tulang attended by students in grades 4 and 5 and accompanied by teachers. The activity consists of 3 stages, including the preparation stage, followed by the implementation stage, and closing with the evaluation stage. The activity was carried out by the Andalas Nagari IV Koto Hilie University KKN Team which is a collaboration from various departments. It is hoped that the results of this community service can shape students' attitudes and behavior towards improving health, especially in choosing healthy snacks and nutritious food at school and at home. During the implementation of this community service activity, students and teachers actively participated in this activity. Through the evaluation carried out at the end of the event, students and teachers gave positive responses, and it is hoped that similar activities can improve the understanding and skills of teachers and students at SDN 03 Bukit Tambun Tulang.